2015
DOI: 10.1038/ncomms7949
|View full text |Cite
|
Sign up to set email alerts
|

Subcontinuum mass transport of condensed hydrocarbons in nanoporous media

Abstract: Although hydrocarbon production from unconventional reservoirs, the so-called shale gas, has exploded recently, reliable predictions of resource availability and extraction are missing because conventional tools fail to account for their ultra-low permeability and complexity. Here, we use molecular simulation and statistical mechanics to show that continuum description—Darcy's law—fails to predict transport in shales nanoporous matrix (kerogen). The non-Darcy behaviour arises from strong adsorption in kerogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
316
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(331 citation statements)
references
References 41 publications
15
316
0
Order By: Relevance
“…Falk et al used molecular simulation and statistical mechanics to show the transmission behavior of hydrocarbon in shale nanoporous matrix, the results demonstrated that the Darcy's law fails to predict the transport of shale gas at the nanoscale. In particular, when studying on the transmission mechanism of shale gas in disordered pores, the influence of permeability, porosity and tortuosity should be considered [53]. It was found that whether the gas is adsorbed on coal or shale, the organics structure is the main research object.…”
Section: Introductionmentioning
confidence: 99%
“…Falk et al used molecular simulation and statistical mechanics to show the transmission behavior of hydrocarbon in shale nanoporous matrix, the results demonstrated that the Darcy's law fails to predict the transport of shale gas at the nanoscale. In particular, when studying on the transmission mechanism of shale gas in disordered pores, the influence of permeability, porosity and tortuosity should be considered [53]. It was found that whether the gas is adsorbed on coal or shale, the organics structure is the main research object.…”
Section: Introductionmentioning
confidence: 99%
“…Extracting the mass term directly from MD simulations paves the way to the study of isotopic effects. It can also be used to quantify in a well-defined way the number of molecules brought along ions during transport or to interpret the peculiar behaviour of the friction on alcanes as a function of chain length [29,30]. In particular, it provides a microscopic route to model acoustophoresis [31,32] or electro-osmotic effects [33,34].…”
Section: Figmentioning
confidence: 99%
“…However, different from water transport in micropores, the governing physics of water transport in nanopores become various boundary conditions (slip flow or multilayer sticking), caused by wettability, and viscosity variation in nanopores, caused by strong interactions from nanopore wall (Monteiro et al 2012;Falk et al 2015;Klein and Kumacheva 1995;Neto et al 2005). In this paper, an improved model was proposed based on Wu et al's work (2017).…”
Section: Introductionmentioning
confidence: 99%